Analisis Kebutuhan Media Kuartet RIASEC untuk Meningkatkan Pemahaman Karir Sesuai Kepribadian Siswa - Zahrani, Sarah Shafa; Sinring, Abdullah; Amirullah, M.; Ayu, Siska Putri (Universitas Muhammadiyah Magelang, 2026)
The purpose of this study was to analyze the need for the development of RIASEC quartet media as a career guidance media in improving career understanding according to the personality of class X and XII students at MAN Kepulauan Selayar. This research used a descriptive qualitative approach with data collection methods through in-depth interviews with counseling teachers. The results of the interview show that most students at MAN Kepulauan Selayar, especially classes X and XI have never received career guidance and personality tests that have not been evenly distributed. This means that career preparation is not optimal. In addition, the BK teacher argued that guidance and counseling services at school are still conventional with the lecture method and have not been supported by innovative media in helping students improve career understanding according to their personality. RIASEC quartet media is considered relevant because it displays the types of professions and their characteristics based on personality types that are easy to understand. This research shows that the development of RIASEC quartet media is important as an innovation in career guidance services to increase career understanding according to the personality of students. Keywords: needs analysis, career guidance media, quartet